Living in mixed-sex groups limits sexual selection as a driver of pelage dimorphism in bovids. (4th March 2022) - D'Ammando, Giacomo; Franks, Daniel W; Bro-Jørgensen, Jakob
Abstract: Among mammals, bovids provide some of the most striking examples of sexual dimorphism in colouration and pelage appendages, such as beards and manes. This dimorphism is usually assumed to have evolved through sexual selection on males in the context of intra- or intersexual communication. However, the sexes coloration and pelage appendages look similar between the two sexes in several bovid species thought to be characterized by large opportunities for sexual selection, hinting at fitness costs of dimorphic traits due to other selection pressures. This study applies the comparative method with phylogenetic control to identify the factors promoting and constraining the evolution of dimorphism in coloration and pelage appendages across bovids. We found that trait dimorphism correlated positively with large breeding group size, an indicator of the intensity of sexual selection, and negatively with male territoriality, which is also likely to affect the operation of sexual selection. The relative rarity of color and pelage dimorphism in species with territorial mating systems may be explained by weaker sexual selection due to difficulty in monopolizing females and/or sexual selection targeting other traits, such as territorial quality as an extended phenotype. We also found that dimorphism in color and pelage was reduced in species spending more time in mixed-sex groups outside the breeding season, possibly due to increased predation costs from non-uniformity. This suggests that benefits from integration into mixed-sex groups select against the extravagant male morphologies otherwise promoted by sexual selection. Abstract : If sexual selection is such a powerful force in nature, why are the sexes strikingly similar in some of the bovid species where the competition for mates is believed to be most intense? This study finds that although sexual dimorphism in coloration and pelage appendages generally characterizes species where the potential for males to monopolize females is high, such dimorphism is less common in species where the sexes tend to form mixed-sex groups outside the breeding season. We propose that a predation cost from divergent appearance of the sexes may be higher in taxa that form mixed-sex groups.